2006
DOI: 10.1016/j.jeurceramsoc.2005.03.236
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and crystal growth of glasses produced by a generic plasma arc-process

Abstract: The feasibility to crystallise a glass prepared by thermal plasma vitrification of hospital wastes to produce a glass-ceramic suitable to be used as a construction material was investigated by using differential thermal analysis (DTA) and X-ray diffraction (XRD). Two crystallisation exotherms in DTA were attributed to the formation of wollastonite and a crystalline phase belonging to the melilite group (gehlenite or akermanite). DTA tests have shown that the glass is not suitable for bulk crystallisation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…The T f and T m varied with the heating rate. Other authors found T g heating rate dependency [2,24]. It is evident that T f increases incrementally with increasing ZrO 2 content from 515 °C to 522 °C for the series A to E. Addition of ZrO 2 will increase the number of bridging oxygens per silicon atom and the presence of Zr 4+ ions will impart a higher packing density and higher T g .…”
mentioning
confidence: 84%
“…The T f and T m varied with the heating rate. Other authors found T g heating rate dependency [2,24]. It is evident that T f increases incrementally with increasing ZrO 2 content from 515 °C to 522 °C for the series A to E. Addition of ZrO 2 will increase the number of bridging oxygens per silicon atom and the presence of Zr 4+ ions will impart a higher packing density and higher T g .…”
mentioning
confidence: 84%
“…They can also be prepared from cheaper raw materials such as wastes because the glass-ceramic process has been established as a suitable way to valorise mining and industrial wastes [29,30], including fly ash from incineration [31,32] and thermal power plants [4,33], wastes from hydrometallurgical processing plants [30], residual glass fibres from polyester matrix composites [34] and bagasse ashes [8], among others wastes. One residue that has experienced a significant increase in production in recent years is biomass ash, which originates from the combustion of biological material for energy purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Glass-ceramics from PG glass were prepared by a sintering route reported in a previous work 21 . The glass powder was ground in a ball mill and sieved to <200 µm.…”
Section: Methodsmentioning
confidence: 99%